(untitled) (International Seven Journal of Health Research, 2024)
Severe acute bronchiolitis is mostly caused by the respiratory syncytial virus (RSV) and is the main cause of hospitalization in children under one year old. Although it has a low mortality rate, it has a high morbidity rate, requiring early diagnosis through a detailed clinical history and physical examination. A narrative review of fourteen articles found in the PubMED/MEDLINE, SciELO and BVS electronic databases was therefore carried out, with the aim of reviewing the most up-to-date literature on the subject. Currently, the monoclonal antibody Palivizumab is the main agent used to prevent bronchiolitis and is available for patients at high risk of developing the serious disease. In addition, the Abryso vaccine was recently approved by the National Health Surveillance Agency (Anvisa) and will be administered to pregnant women in the last trimester of pregnancy, with the aim of preventing the disease in newborns. Finally, it was found that the appropriate management of acute viral bronchiolitis consists of supportive measures such as hydration, nutritional support and oxygenation when necessary, while the use of corticosteroids and bronchodilators has not been shown to reduce the length of hospital stay or the natural course of the disease.